Reconstruction of Holistic Benefits in Resolution of Wakf Land Disputes in Palembang - Pradana, Surya; Holijah; Syafran Afriansyah (Nurani, 2025)
Waqf constitutes a significant instrument in enhancing social, cultural, economic, and educational well-being, as it represents the voluntary dedication of assets by a waqif for religious and public benefit purposes. However, the complexity of waqf administration, assets, and legal aspects often give rise to disputes that require in-depth handling and study. This study aims to identify the causes of waqf land disputes in Palembang and formulate a comprehensive conflict resolution framework. The study employs a qualitative research design grounded in a sociological perspective to examine the dynamics of waqf implementation and emerging disputes in Kemuning District, Palembang City. Data were collected through observation, interviews, and documentation, then analyzed thematically using sociological theory as well as the framework of Islamic law and waqf law. The results show that immovable waqf assets significantly influence social dynamics and are often the main source of disputes, most of which end up in religious courts. Disputes are generally triggered by the sale of waqf assets, changes in their intended use, adoption issues, and ownership claims by the waqf family. The causes of disputes can be classified into internal and external factors. Internal factors include the low understanding and capacity of nazhir, the involvement of heirs, administrative costs, and negligence in waqf management. External factors include minimal public awareness of waqf, the dominance of private interests, weak government attention, and a suboptimal administrative system. These findings highlight the urgency of adopting a comprehensive dispute resolution framework that integrates deliberation, judicial and non-judicial mechanisms in line with national law, alongside mediation with relevant institutions, to safeguard and sustain waqf assets.